PENDAMPINGAN LITERASI DAN NUMERASI ANAK USIA SEKOLAH DASAR DI SDN 1 NAIONI KOTA KUPANG MELALUI PENGABDIAN MASYARAKAT PROGRAM STUDI PGSD FKIP UNIVERSITAS MUHAMMADIYAH KUPANG - Sanusi, Nurul Istiqomah; Muliandani, Nani; Muhsam, Julhidayat; Khasna, Fenny Tanalinal; Nuriyah; Syahril Muh, Abdul (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The community service program aims to: 1) improve the literacy and numeracy of elementary school-age children; 2) reduce the addiction of elementary school-aged children to playing online games; and 3) help parents pay more attention to their children's learning of literacy and numeracy in Naioni Village. Formal community service activities are carried out by making tutoring in literacy and numeracy available. The subjects of the service are elementary school-age children and their parents. Activities are carried out in stages, including planning, observation, technical implementation, program implementation, and evaluation. The results of community service obtained have succeeded in: 1) improving the literacy and numeracy abilities of elementary school-aged children; 2) reducing the addiction of elementary school-aged children to playing online games; and 3) helping parents pay more attention to their children's learning of literacy and numeracy in Naioni Village.